Grasping the interdisciplinarity of mechatronics. - Siegwart, R.
The two technical universities of Switzerland, the Swiss Federal Institute of Technology of Lausanne (EPTL) and Zurich (ETHZ), have a long tradition in mechatronics education. One successful part of this education at ETHZ is a lecture called Smart Product Design with a main emphasis on hands-on experience. Apart from providing the basics of mechatronics, the students work on a real mobile robot system during the course. Each student team receives a mobile robot kit, based on a Motorola 68332 microcontroller. Each year's course ends with a competition between the fully autonomous robots of the interdisciplinary student teams. In the recent years' competitions the students had to build robots to autonomously construct towers, to play golf or soccer, or to collect Lego students to bring them to school. The article briefly discusses the important aspects of mechatronics education and then focuses on the Smart Product Design course at ETHZ, discussing the lecture, the laboratory work, and the experience gained during the last eight years
Keywords: Motorola 68332 microcontroller; Smart Product Design; Fully autonomous robots; Hands-on experience; Interdisciplinarity; Laboratory work; Mechatronics education; Mobile robot kit